From the Essence of Beauty to a Riddle of Death: a Roman Incineration Grave in the Goveja Quarter of the Town of Vis (Archaeologia Adriatica, 2023)
The paper presents finds discovered in the the area of Goveja in the town of Vis on the island of the same name. The characteristics and the context of the finds suggest that they might have belonged to a Roman incineration grave. Prominent among the finds is a unique ceramic vessel, in the described context used as an urn. Its typical morphological model – a skyphos with a barbotine decoration – suggests that the vessel was manufactured in a Pontic sigillata workshop, that is in one of the Black Sea or Eastern Mediterranean production centres. Its uniqueness is reflected in the elaborate relief added to it, very reminiscent of decorative details found in other objects – appliqués from a fulcrum of a cline – that have been interpreted as a depiction of Artemis/Diana. The detailed analysis and contextualisation of grave finds presented in this paper shed further light on the manufacture of and demand for late 1st century and 2nd century tableware, and open new questions as to the appearance and distribution of Issaean burial landscapes, as well as the specific features of the Issaean funerary rite.
Keywords: Vis; Roman Issa; Roman incineration grave; Pontic pottery; relief depiction of Artemis/ Diana; glass unguentarium; Roman funeral rite